Analisis Pusat Pertumbuhan Ekonomi Pada Tingkat Kabupaten/Kota Di Provinsi Nusa Tenggara Timur - Maria Lidwina Meo; Fransina W. Ballo; Maria I. H. Tiwu (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to analyze the center of economic growth at the district / city level in NTT Province. The method used is statistical description with a qualitative approach. The focus of this research is to observe and find out the mainstay economic sector of each Regency / City in East Nusa Tenggara Province which can also determine the economic position of each Regency / City, using data collection techniques obtained from various sources in the form of books, journals, websites as well as the results of publications of institutions or government agencies such as the Statistical Agency (BPS) by taking data related to the problem studied, Analyzed using LQ analysis methods and klassen typology analysis. The results of the study using LQ (Location Quention) Analysis analysis show that each base sector in each Regency/ City in East Nusa Tenggara Province has 15 economic sector bases, and Based on the results of klassen typology analysis in 20 Regencies and 1 City in East Nusa Tenggara Province in 2019-2023 it was found that there are 18 districts/cities in East Nusa Tenggara Province in quadrant I (Fast forward and fast growing regions), 2 districts/cities in quadrant II (Developed But Depressed Regions), and 1 district/city in quadrant III (Fast Developing Regions).